2021
DOI: 10.1161/jaha.121.021873
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Ratio of Acceleration Time/Ejection Time and Mortality in Patients With High‐Gradient Severe Aortic Stenosis

Abstract: Background The ratio of acceleration time/ejection time (AT/ET) is a simple and reproducible echocardiographic parameter that integrates aortic stenosis severity and its consequences on the left ventricle. No study has specifically assessed the prognostic impact of AT/ET on outcome in patients with high‐gradient severe aortic stenosis (SAS) and no or mild symptoms. We sought to evaluate the relationship between AT/ET and mortality and determine the best predictive AT/ET cutoff value in these patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…The opposite was observed in the prevalence of SF without LF, a condition which was more frequent in patients with SAS compared to those without. This was also observed in other AS study cohorts [ 11 , 18 ] ( Figure 7 ). Both the lower frequency of LF without SF and the higher frequency of SF without LF in SAS patients are related to higher LVET values and support the independent role of AS in prolonging LVET.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The opposite was observed in the prevalence of SF without LF, a condition which was more frequent in patients with SAS compared to those without. This was also observed in other AS study cohorts [ 11 , 18 ] ( Figure 7 ). Both the lower frequency of LF without SF and the higher frequency of SF without LF in SAS patients are related to higher LVET values and support the independent role of AS in prolonging LVET.…”
Section: Discussionsupporting
confidence: 87%
“…We assessed LV forward flow using SVI, with a 35 mL/m 2 cutoff value for LF [ 1 , 2 ], and FR, with a 210 mL/s cutoff value for SF [ 11 ]. In recent years, SF has been reported to identify the flow reduction that may induce pseudosevere AS [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the rapid opening of the aortic valve is a valid assumption in healthy individuals, this is not the case in those suffering from stenosis due to the prolonged opening time [ 21 ]. Studies have shown that the ratio of acceleration time—the required time to reach a maximum aortic flow—to the total ejection time increases as the severity of aortic stenosis increases [ 21 , 22 , 23 ]. Virag et al [ 24 ] used the lumped parameter model of the left ventricle and arterial system coupling, and the motion of the aortic valve area was defined as a function of volume displaced by leaflets during the opening and closure phases in systole.…”
Section: Introductionmentioning
confidence: 99%